2023
DOI: 10.1002/anie.202304722
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐fueled Mechanical Motions with Dynamic Phosphorescence Induced by Topochemical [2+2] Reactions in Organoboron Crystals

Abstract: In the quest for essential energy solutions towards an ecological friendly future, the transformation of visible light/solar energy into mechanical motions in metal‐free luminescent crystals offers a sustainable choice of smart materials for lightweight actuating, and all‐organic electronic devices. Such green energy‐triggered photodynamic motions with room temperature phosphorescence (RTP) emission in molecular crystals have not been reported yet. Here, we demonstrate three new stoichiometrically different Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Multiply charged supramolecular polymers were accessed by BÀ N LP formation between diborylated imidazolium-based ionic liquids and pyrazine or 1,4-diazabicyclo-[2.2.2]octane. [31] Matsumi and co-workers reported that these polymers were soluble in highly polar solvents such as methanol, showing 11 B NMR signals in the expected region of tetracoordinate boron. Lithium ion conductivities of up to 8.8 × 10 À 6 S cm À 1 at 51 °C were measured in the presence of equimolar amounts of lithium triflimide, LiNTf 2 .…”
Section: Polymers Derived From 'Classical' Lewis Pairsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiply charged supramolecular polymers were accessed by BÀ N LP formation between diborylated imidazolium-based ionic liquids and pyrazine or 1,4-diazabicyclo-[2.2.2]octane. [31] Matsumi and co-workers reported that these polymers were soluble in highly polar solvents such as methanol, showing 11 B NMR signals in the expected region of tetracoordinate boron. Lithium ion conductivities of up to 8.8 × 10 À 6 S cm À 1 at 51 °C were measured in the presence of equimolar amounts of lithium triflimide, LiNTf 2 .…”
Section: Polymers Derived From 'Classical' Lewis Pairsmentioning
confidence: 99%
“…Even cooperative N 2 activation has been achieved with a diboraanthracene‐samarocene pair [9d] . B−N LP formation has also been exploited to position photoactive molecules in close proximity to one another in a way that allows for topochemical [2+2] olefin photodimerization to occur rapidly (e.g., 5 ) [10] or to trigger visible light‐fueled photomechanical processes [11] . Finally, B−N LP formation has been exploited to modulate the electronic structure and photophysical properties of π‐conjugated organic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic light-emitting crystals composed of π-conjugated molecules can be applied in sensors, [1] optical waveguide devices, [2] smart materials. [3][4][5][6][7] These crystals have attracted great interest from the scientific community. Some stimuliresponsive materials can convert light, thermal, or mechanical energy into mechanical motion at the macro-, micro-, or nano-scale, making them promising materials for various applications, such as light harvesting, mechanical actuation, molecular mechanics, smart switches, and optical sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Organic light‐emitting crystals composed of π‐conjugated molecules can be applied in sensors, [1] optical waveguide devices, [2] smart materials [3–7] . These crystals have attracted great interest from the scientific community.…”
Section: Introductionmentioning
confidence: 99%